TO THE QUESTION OF THE ADMINISTRATION ALTERNATIVE FORMS SETTLEMENT OF PUBLIC-LEGAL DISPUTES FOREIGN COUNTRIES - Sarpekov , Рамазан Кумарбекович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The authors of this article consider an alternative form of pre-trial settlement of public disputes in foreign countries. In recent years, this form has gained immense popularity and widespread recognition, especially among foreign lawyers. This form of conflict resolution finds its place in Central Asian countries, including Kazakhstan. The study used theoretical methods of analysis and comparison of legislative acts of foreign countries in the field of alternative methods of resolving public disputes. Analysis of foreign experience shows that the process of formation and development of alternative forms of pre-trial settlement of disputes is due to natural causes. Relevant reasons distinguish the search for the most expeditious, effective and cost-effective solution of disputes between administrative bodies and natural or legal persons. It should be noted that this form of resolving disputes does not carry the purpose of depriving citizens of their constitutional rights to judicial protection, but only allows them to expand the range of dispute resolution without the intervention of judicial bodies. The current stage of administrative reform is inextricably linked with the further democratization of the institutions of society and the state and the improvement of administrative procedures, legal support of the latest management methods and technologies. Among the emerging mechanisms for resolving various social conflicts, a special place is occupied by the institution of citizens' appeal to state bodies and to state officials, as a form of their participation in government and a way to protect their rights and freedoms. We believe it is necessary to note that today among academic administrators is a debatable discussion of the concept of «alternative dispute resolution».